(untitled) (Journal of Asian Development Studies, 2025)
This research paper examines the critical intersection of climate change and food security, with a specific focus on policy responses within the world’s most climate-vulnerable regions as of 2025. As anthropogenic climate change transitions from a projected risk to an active driver of systemic instability, regions such as the Sahel, South Asia, and Small Island Developing States (SIDS) face unprecedented threats to the four pillars of food security: availability, access, utilisation, and stability. Utilising a multi-dimensional qualitative framework and comparative policy analysis, the study evaluates the efficacy of contemporary interventions, including Climate-Smart Agriculture (CSA), anticipatory cash transfers, and weather-indexed insurance. The findingsreveal a significant "policy-implementation gap," where technological solutions are often stymied by socio-economic fragility and a lack of decentralised climate finance. Results indicate that while anticipatory actions have successfully mitigated immediate hunger, long-term resilience is undermined by declining crop nutritional density—driven by elevated CO_2 levels—and nationalistic trade policies such as export bans. The paper argues that current reactive aid models must be replaced by a paradigm of anticipatory governance and regional cooperation. It concludes by outlining practical implications for a nutrition-sensitive agricultural shift and for reforming global financial mechanisms, such as the loss and damage fund. Ultimately, the study asserts that global food stability in an era of environmental volatility depends on integrating biophysical adaptation with equitable socio-economic policy to bridge the resilience divide.